2014
DOI: 10.1016/j.jval.2014.08.2330
|View full text |Cite
|
Sign up to set email alerts
|

Real World Data in Oncology: Third- and Fourth-Line Treatments Administered in Metastatic Colon-Rectal Cancer (MCRC)

Abstract: and retrieved from an extra boost of ONCOVIEW database. ONCOVIEW is a continuous syndicated study on cancer treatment in the hospital setting, based on the collection of patient questionnaires. Patients inclusion criteria were the presence of an mCRC diagnosis, 3rd or later actual therapy line and no participation in a phase II or III clinical study. Information collected included patient demographic characteristics, mCRC characteristics (TNM Classification, Karnofsky performance status scale and mutation anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…As multiple chemotherapeutic and targeted biologic agents emerged, treatment patterns and sequences for mCRC patients have significantly evolved over the past decade [12]. Several studies have reported the complex and changing treatment pattern among mCRC patients in the United States [13][14][15][16], Canada [17], and some European countries [18,19]. However, there is a lack of key real-world evidence on the clinical characteristics and treatment patterns of CRC/mCRC patients in China.…”
Section: Introductionmentioning
confidence: 99%
“…As multiple chemotherapeutic and targeted biologic agents emerged, treatment patterns and sequences for mCRC patients have significantly evolved over the past decade [12]. Several studies have reported the complex and changing treatment pattern among mCRC patients in the United States [13][14][15][16], Canada [17], and some European countries [18,19]. However, there is a lack of key real-world evidence on the clinical characteristics and treatment patterns of CRC/mCRC patients in China.…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective comparison between trifluridine/tipiracil and regorafenib in 200 patients demonstrated that the majority of patients treated with third-line agents were fit patients 9. In addition, an overview of patient profiles in the refractory setting demonstrated that patients receiving third-line or fourth-line treatment for mCRC had a European Cooperative Oncology Group (ECOG) PS of 0 or 1 10. Data provided by phase III clinical studies correspond only to ECOG 0 or 1 patients, while real-world evidence coming from the REBECCA cohort, the CORRECT and RECOURSE trials, and Spanish real-world data includes also a subset of patients with ECOG >1, suggesting thereby that this subset of patients is not represented in clinical trials.…”
Section: Treatment Goals According To Line Of Therapymentioning
confidence: 99%
“…Aproximadamente 25% dos pacientes apresentam metástase no momento do diagnóstico e cerca de 50% apresentarão metástase durante o curso da doença, contribuindo para uma elevada taxa de mortalidade relacionada a esse tipo de câncer (Van Cutsem et al, 2014). Dos pacientes com CCRm, apenas 28% recebem tratamento em terceira linha (Abrams et al, 2014) e, embora a doença esteja em um estágio mais avançado, esses pacientes ainda estão aptos a receber tratamento, sendo fundamental uma opção terapêutica adequada e otimizada para essa fase (Chibaudel et al, 2012;Heiman et al, 2014).…”
Section: Introductionunclassified